Beauty as an example of nonempirical criterion of the scientific theory choice - Ciszewska, Diana; Szydłowski, Marek (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2010)
It is sometimes argued that beauty and science have nothing in common. This is not necessarily true. When speaking of beauty in science we are touching two branches of knowledge: aesthetics and physics. We show that they are connected, permeate each other and work together to give good scientific results. Scientific theories and aesthetics theories exhibit some similarities not only during the creation phase, but also during the application phase. We examine two aesthetic criteria, namely symmetry and simplicity, which are valuable tools in choosing the correct scientific theory.